Խաչատուր վարդապետ Էրզրումեցին՝ բանաստեղծական արուեստի եւ կլասիցիզմի տեսաբան - Հենրիկ Բախչինեան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Архимандрит Хачатур Эрзрумеци (1666–1740) — крупный энциклопедист своего времени, автор многочисленных трудов, относящихся к ряду отраслей науки. Он первым привнес европейскую теоретическую мысль в армянскую действительность. Ценнейшей работой Эрзрумеци является двухтомное энциклопедическое исследование под названием «Краткая философия» (Венеция,1711). Archimandrite Khachatur of Erzurum (1666–1740) is a great encyclopedist of his time, author of numerous works related to a number of branches of science. He was the fi rst to introduce European theoretical thought into Armenian reality. The most valuable work of Khachatur of Erzurum is the two-volume encyclopedic study called “Brief Philosophy” (Venice, 1711).
Keywords: Literature